APLIKASI METODE PERAMALAN HOLTH WINTERS EXPONENTIAL SMOOTHING PADA DATA JUMLAH KEJADIAN HIPERTENSI - wisoedhanie widi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2019)
In the effort to see and examine the situation and conditions that occur in the future should be done forecasting. Hypertension occupies the order of the top ten diseases in the Puskesmas together and almost every month occurs a new case of hypertension, so that the incidence of hypertension become a trend and should be done forecasting. The purpose of this research is to practice the data on the number of hypertensive events in Puskesmas with the city of Malang using Holth Winters Exponential Smoothing method. The type of research used is non reactive research which is a type of research for secondary data. The sample Unit in this study is a patient who comes to medicine and is recorded as a hypertensive patient in the Puskesmas with the city of Malang. From 2013 to 2016. Research Data is processed using Minitab software. The results of this study showed the incidence of hypertension for the year 2018 decreased, with the lowest occurrence rate occurring in December of as many as 58 occurrences. The presence of a trend in the incidence of hypertension can be supported by internal factors, namely gender; and external factors, namely the environment. Outside in this study is research article, Trend morbidity graph figures incidence of hypertension disease in Puskesmas and study as teaching materials. Through the results of this research, the Puskesmas advised the party to develop planning and control of work for eradication and transmission of hypertensive disease (P2P).